EFFECT OF PERCEPTION OF QUALITY, PRICE, ITS REPUTATION AND CUSTOMER SATISFACTION ON PURCHASE DECISION AVIATION SERVICES (Case Study: Customer Services Flights PT. Lion Air) - Simanihuruk, Peran (UNIKA Santo Thomas, 2016)
The purpose of this study to analyze the influence of perceived quality, price, the company's reputation and customer satisfaction partially and simultaneously to the purchase decision-making aviation services. Benefits Research, provide empirical evidence about the influence of the variables that can influence the purchasing decision of customers, and provide a solution in the form of advice to the management of these variables. For the community. providing knowledge to the community, especially for those who want to engage in the world of business and relating to the maintenance of the brand as well as maintaining the presence of the customer. For education, contributing to the academic community about the importance of managing the variables that can influence the purchasing decision of the consumer through the perception of quality, price, the company's reputation and customer satisfaction. Total sample of 96 respondents, the method of collecting data through questioner and documentation, methods of data analysis by regression. The results of the regression equation: PKP = 10.034 + .018 + PK 0,873H 0,17RP + .705KP. meaning that the variable perception of quality, price, the company's reputation and customer satisfaction has a positive influence on the purchase decision aviation services. Of the four variables that have more influence on the purchase decision is the variable price of aviation services. The correlation coefficient variable perception of quality, price, the company's reputation and customer satisfaction to the purchase decision aviation services have a very strong relationship with the value of r = .743. The coefficient of determination of r2 = .552049, meaning that the variable perception of quality, price, reputation and customer satisfaction Company was able to explain 55.2% of the purchase decision-making airline, while 44.8% are influenced by other factors. Based on t test, t value (Price and Customer Satisfaction)> t table means in partial, price and customer satisfaction has a significant influence on the purchase decision-making aviation services. While the t (perception of the quality and reputation of the company) â‰¤ t partial table does not have a significant influence on the purchase decision-making aviation services. By F test, F count (variable perception of quality, price, the company's reputation and customer satisfaction)> F table, meaning that simultaneous variables has a significant influence on the purchase decision aviation services. Based on the results of the study should the company need to increase the perception of quality through improved service quality and reputation of the company through increased attributes offered through its products. Customer satisfaction and price becomes the center of attention of the customer, then the management should still be able to maintain it so that it has a very high competitiveness